Examining the effect of visual treatments on truck drivers' time-to-arrival judgments of motorcycles at T-intersections - Law, Teik Hua; Ghanbari, Mahshid; Hamid, Hussain; Abdul-Halin, Alfian; Ng, Choy Peng (Elsevier, 2015)
An automobile–motorcycle crash most commonly results when an automobile pulls out of a side road into the path of an oncoming motorcycle and violates the motorcyclist’s right-of-way. One of the reasons for this could be that motorists misjudged the motorcycle arrival time. Motorcyclists are particularly vulnerable to injury in crashes with truck due to substantial differences in vehicle mass, protection degree and speed. We investigated truck drivers’ judgments of motorcycle time-to-arrival (TTA) across a number of visual treatments. Participants watched a series of video clips captured at a T-intersection, and they were instructed to respond by clicking the computer mouse at the time they estimated the front wheels of an oncoming vehicle (motorcycle or car) to reach the T-intersection. The results showed that, at long distance between the target motorcycle and the viewer, the motorcycle with daytime running headlights (DRH) was estimated to arrive sooner than the motorcycle whose motorcyclist wore a black helmet with a reflective sticker. However, the opposite is true at a short distance. We also found that a motorcyclist wearing a white helmet and riding a motorcycle with DRH, as well as a motorcyclist wearing a white helmet and white outfit, would improve truck drivers’ judgment with respect to motorcycle TTA. Consequently, truck drivers would be less likely to pull out into a small gap in front of a motorcycle, resulting in a higher safety margin for the motorcycle.